The road's end - Kirk, Daniel (Amulet, 2011)
Fourteen-year-old Matt, Tuava-Li the elf, and Tomtar the troll continue their race to the North Pole to try to save their worlds, in competition with Becky and the villainous Jardaine, but unexpected horrors await whoever journeys beyond the Gates of Vattar.